2023
DOI: 10.3390/nu15051192
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products in Precision Oncology: Plant-Based Small Molecule Inhibitors of Protein Kinases for Cancer Chemoprevention

Abstract: Striking progress is being made in cancer treatment by using small molecule inhibitors of specific protein kinases that are products of genes recognized as drivers for a specific type of cancer. However, the cost of newly developed drugs is high, and these pharmaceuticals are neither affordable nor accessible in most parts of the world. Accordingly, this narrative review aims to probe how these recent successes in cancer treatment can be reverse-engineered into affordable and accessible approaches for the glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…NPs are a wide range of bioactive components isolated from natural organisms, including plants, animals, insects, marine organisms ( Manoharan and Perumal, 2022 ), and microorganisms. NPs are attractive sources for developing new medicinal and therapeutic agents ( Thomford et al, 2018 ; Thompson and Lutsiv, 2023 ; Rao et al, 2019 ). For a long time, NPs have been regarded as a rich source of the active ingredients in new drugs.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…NPs are a wide range of bioactive components isolated from natural organisms, including plants, animals, insects, marine organisms ( Manoharan and Perumal, 2022 ), and microorganisms. NPs are attractive sources for developing new medicinal and therapeutic agents ( Thomford et al, 2018 ; Thompson and Lutsiv, 2023 ; Rao et al, 2019 ). For a long time, NPs have been regarded as a rich source of the active ingredients in new drugs.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Specifically, we have proposed that the chemical diversity of a food pattern can be predicted by understanding the botanical origin of those foods [65]. More recently, we have used the same botanical approach to illustrate that small-molecule inhibitors, e.g., protein kinase inhibitors, are found in the same botanical families from which human foods are derived and that the nature of the protein kinases inhibited varies by botanical family [66]. At this juncture, we are unaware of the use of this approach either in assessing the activity of effective dietary patterns or as the rationale for formulating precision dietary patterns based on their demonstrated activity in inhibiting oncogenic protein kinases.…”
Section: Protein Kinasesmentioning
confidence: 99%
“…One such drug acts against a checkpoint protein called CTLA-4. So far, the six approved ICIs include (1) PD-1 inhibitors, such as pembrolizumab, nivolumab, and cemiplimab; (2) anti-PD-L1 inhibitors, including atezolizumab, and durvalumab; and (3) ipilimumab, an anti-CTLA-4 inhibitor (66). ICIs are the standard for the treatment of metastatic and unresectable, stage 3 non-small cell lung cancer.…”
Section: Immune Checkpointsmentioning
confidence: 99%
“…Thus, it is imperative to develop new and effective methods for cancer treatment. One of the most important strategies for fighting cancer is chemoprevention, defined as the use of natural or synthetic compounds as drugs or through the diet for the prevention or even the reversal of carcinogenesis [ 2 , 3 ]. In recent years, intensive research interest for anticancer compounds found in marine organisms has been performed.…”
Section: Introductionmentioning
confidence: 99%